Impact of Parenting Style on Early Childhood Learning: Mediating Role of Parental Self-Efficacy - Kong, Chuibin; Yasmin, Fakhra (Frontiers in Psychology, 2022)
The current study examined the impact of parental style on children's learning outcomes among Chinese high school students, as well as the role of parental self-efficacy (PSE) as a mediating factor. In the domains of education and psychology, it is increasingly recognized that parents have a considerable impact on their children's learning and development. Purposive sampling was used and data was gathered over 3 months from high school children’s parents. Hypotheses were tested using smart partial least squares-structural equation modelling (PLS-SEM v3.2.8) software. The findings of the present study reveal that an authoritative parenting style is positively associated with learning outcomes among Chinese students. Moreover, the mediating role of parental self-efficacy has been tested and proved to be a potential mediator between parental style and children's learning outcomes. High PSE is linked to parents' adoption of a variety of optimum parenting practices throughout childhood, including maternal sensitivity and responsiveness to children's needs, warm and affectionate parental behavior, and monitoring. Hence, low PSE has been linked to coercive or harsh parenting as well as a proclivity to give up easily when faced with parental difficulties. In China, further study is needed on the relationship between parenting style, parental self-efficacy, and learning outcome. Future parenting programmes could also focus on raising parents' understanding of the need for both parents' involvement in expressive activities and mentoring. This could help them boost their parenting self-efficacy even more. Lastly, the implications for parents, children, and teachers are discussed.